Feed digestion of growing Saanen goats - Leite, Rafael Fernandes [UNESP] (2015)
The main objective was to assess the contribution of different segments of the gastrointestinal tract (GIT) to the fiber digestion. Two experiments were conducted, which mean retention time (MRT) of particulate and liquid matter, pool size, and tissues weight in different segments were determined by slaughter technique. The study one evaluated MRT of particulate and liquid matter in growing Saanen goats of different sexes and subjected to different levels of feed restriction. Fifty-four Saanen goats (18 each of females, castrated males and intact males) were used in a 3×3 factorial arrangement comprising the three sexes and three levels of feed restriction (unrestricted/ad libitum, moderate and severe restriction). Polynomial contrasts were used to determine linear and quadratic effect of feed restriction, while the effect of sex was compared by Tukey test. The effects of sex and the interaction between sex and feed restriction were not significant on most of variables evaluated. In conclusion, the level of feed restriction increased the MRT of particulate and liquid matter. The MRT was an important mechanism to increase nutrient supply when animals were subjected to feed restriction, as indicated by increased total tract digestibility. The second study examined physiological aspects in the digestion of fiber, particulate and liquid matter residence, pool size, and tissues weight in the whole tract of growing Saanen goats. A total of 58 Saanen goats were disposed in a 3×3 factorial arrangement consisting of three sexes (female, castrated males, intact males) and three slaughter weights (target BW 16, 23, and 30 kg at slaughter). Treatment effects were evaluated in a split-plot design, with sex as the main plot and slaughter weight as the subplot. Polynomial contrasts were used to determine linear and quadratic effects of slaughter weight. Thus increased BW at slaughter resulted in greater MRT of particulate and liquid matter in ...